Aspectos morfológicos e produtivos de leguminosas forrageiras submetidas a diferentes frequências de corte - SILVA NETO, Abdias José da (2020)
Forage legumes have great potential for use in animal production systems in the Northeast region of Brazil. The successful management of legumes depends on the definition of the cutting frequency for each species. It is important to know how different species or cultivars respond to the same cutting frequency. The objective was to study morphological, structural and productive characteristics of forage legumes [Stylosanthes spp. cv. Campo Grande; Desmanthus pernambucanus (L.) Thellung and Clitoria ternatea L.] from different origins and growth habits under two cutting frequencies (60 and 90 days). The experimental period started in June 2019 and ended in March 2020. The experimental design was in complete randomized blocks, with subdivided plots and four replications. The significance level was 5% probability. Stylosanthes spp. cv. Campo Grande had a higher number of secondary branches and leaves / branch than the others. Stylosanthes spp. cv. Campo Grande and C. ternatea presented higher IAF than D. pernambucanus, while for light interception, Stylosanthes spp. cv. Campo Grande was superior to D. pernambucanus, but it did not differ from C. ternatea. D. pernambucanus showed a higher stem proportion than other legumes, regardless of the cutting frequency used. D. pernambucanus also showed greater height at 90 days compared to other legumes. At 60 days, however, there was no difference in height in relation to C. ternatea. D. pernambucanus had a strong association with variables related to plant structure and stem production. There was no significant effect of the cutting frequency on the total and leaf productivity, but there was a significant increase on the productivity of stems and pods at the frequency of 90 days in the period of 270 days. Legumes, with different growth habits and origins, differ in morphology and structure, but did not show differences in forage productivity. A cutting frequency of 60 days is recommended for D. pernambucanus if the objective is less production and proportion of stems in the forage produced. The high production of pods at the cuttting frequency of 90 days in Stylosanthes spp. cv. Campo Grande and C. ternatea should be evaluated for effects on the nutritive value of forage and seed production.